2015
DOI: 10.1089/hum.2015.030
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy of Inherited Retinal Degenerations: Prospects and Challenges

Abstract: Because of its favorable anatomical and immunological characteristics, the eye has been at the forefront of translational gene therapy. Dozens of promising proofs of concept have been obtained in animal models of inherited retinal degenerations (IRDs), and some of them have been relayed to the clinic. The results from the first clinical trials for a congenital form of blindness have generated great interest and have demonstrated the safety and efficacy of intraocular administrations of viral vectors in humans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 105 publications
0
29
0
Order By: Relevance
“…RP, a debilitating neurodegenerative disorder, is associated with at least 64 genes encoding mostly rod cell-specific proteins that lead to cell death when improperly formed (56)(57)(58). There is currently no cure available, and although gene therapy interventions recently reached clinical trials, the heterogeneity of gene deficits that cause hereditary neurodegenerative conditions is a fundamental limitation of these studies (26,27,29,(59)(60)(61)(62)(63)(64); this is because the strategy involves a monotherapy, which cannot be used to treat disorders caused by mutations in more than one gene. Thus, a non-gene-specific rescue strategy (11,12) to increase biosynthetic fuel and survival by reprogramming of glycolysis is highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…RP, a debilitating neurodegenerative disorder, is associated with at least 64 genes encoding mostly rod cell-specific proteins that lead to cell death when improperly formed (56)(57)(58). There is currently no cure available, and although gene therapy interventions recently reached clinical trials, the heterogeneity of gene deficits that cause hereditary neurodegenerative conditions is a fundamental limitation of these studies (26,27,29,(59)(60)(61)(62)(63)(64); this is because the strategy involves a monotherapy, which cannot be used to treat disorders caused by mutations in more than one gene. Thus, a non-gene-specific rescue strategy (11,12) to increase biosynthetic fuel and survival by reprogramming of glycolysis is highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic retinal prosthetics such as the Argus II, the only FDA approved treatment for end-stage RP, have been able to restore some visual function to blind patients (Yue et al, 2016). Gene therapy approaches either focus on correcting the inherited defects that cause photoreceptor degeneration (Trapani et al, 2015) or seek to convert surviving neurons in the blind retina into artificial photoreceptors via the expression of optogenetic tools using viral vectors (Busskamp et al, 2010; Lagali et al, 2008). Stem cell-based treatments aim to deliver photoreceptor progenitors or other cells into the blind retina to replace cells lost due to disease (Jayakody et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials have shown efficacy, 3–7 showing that the gene therapy approach holds promise for the treatment of neurodegenerative diseases of the brain and spinal cord, 8–10 retina, 11 glioblastomas, 12 and has the potential to enhance repair after neurotrauma to central 13,14 and peripheral 15,16 nervous systems. AAV has been used to deliver nerve growth factor (NGF) in patients with Alzheimer’s disease, neurturin or glial cell-derived neurotrophic factor in Parkinson’s disease, and insulin-like growth factor 1 in amyotrophic lateral sclerosis.…”
Section: Introductionmentioning
confidence: 99%